Impacts of Deforestation and Climate Variability on Terrestrial Evapotranspiration in Subarctic China - Yao, Yunjun; Liang, Shunlin; Cheng, Jie; Lin, Yi; Jia, Kun; Liu, Meng (Forests, 2014)
Although deforestation affects hydrological and climatic variables over tropical regions, its actual contributions to changes in evapotranspiration (ET) over subarctic China remain unknown. To establish a quantitative relationship between deforestation and terrestrial ET variations, we estimated ET using a semi-empirical Penman (SEMI-PM) algorithm driven by meteorological and satellite data at both local and regional scales. The results indicate that the estimated ET can be used to analyse the observed inter-annual variations. There is a statistically significant positive relationship between local-scale forest cover changes (F) and annual ET variations (ET) of the following form: ET = 0.0377F - 2.11 (R-2 = 0.43, p < 0.05). This relationship may be due to deforestation-induced increases in surface albedo and a reduction in the fractional vegetation cover (FVC). However, the El Nino/Southern Oscillation (ENSO), rather than deforestation, dominates the multi-decadal ET variability due to regional-scale wind speed changes, but the exact effects of deforestation and ENSO on ET are challenging to quantify. http://gateway.webofknowledge.com/gateway/Gateway.cgi?GWVersion=2&SrcApp=PARTNER_APP&SrcAuth=LinksAMR&KeyUT=WOS:000344352900008&DestLinkType=FullRecord&DestApp=ALL_WOS&UsrCustomerID=8e1609b174ce4e31116a60747a720701 Forestry SCI(E) EI 0 ARTICLE yaoyunjun@bnu.edu.cn; sliang@umd.edu; brucechan2003@126.com; yi.lin@pku.edu.cn; jiakun@bnu.edu.cn; xinyin_liumeng@163.com 10 2542-2560 5